Kemitraan Guru Dan Orangtua Dalam Mengembangkan Kemandirian Siswa KB SPMAA Desa Jarorejo Kecamatan Kerek - Nurul Novitasari Novitasari (UIN Kiai Ageng Muhammad Besari, 2022)
This study aims to explain the partnership between teachers and parents in developing the independence of SPMAA family planning students in Jarorejo Village. This research uses qualitative research. The location of this research is in KB SPMAA, Jarorejo Village, Kerek District. Data collection techniques using the method of observation, interviews, and documentation. This study uses primary data sources, namely: head of family planning and teachers, while secondary data researchers use observations that researchers did at KB SPMAA Jarorejo Village and documentation during the activity. Data analysis researchers used 3 stages, namely: data reduction, data presentation, and drawing conclusions. The validity of the data researchers used 3 techniques, namely: triangulation technique, source, time. Based on the process of data collection and data analysis, researchers can conclude several things. The first is a partnership between teachers and parents in the form of a teacher and parent meeting which is held during recess and it discusses what activities will be carried out and informs students about the learning progress of students, parents who help teachers decorate the classroom, parents and teachers exchange stories about the learning process. students and how students develop. Secondly, the development of student independence at this time after parents no longer accompany students in class, from this change, the KB SPMAA students in Jarorejo Village, Kerek District, have now started to be more creative and can do everything themselves without asking for help from others.